OLAHAN SAYURAN MENJADI ES KRIM NABATI PADA IBU-IBU RT 03/04 DIKELURAHAN TAMALANREA JAYA - Khaeriyah Darwis; St. Khadijah Yahya Hiola (Universitas Islam kalimantan MAB, 2018)
This vegetable processing training aims to build the entrepreneurial spirit of RT 03/04 with the utilization of processed red spinach and broccoli vegetables which if developed over the long term will foster a productive economy that can increase family income. In addition, it is hoped that later, ladies and gentlemen, RT 03/04 Tamalanrea Jaya Village is able to form a Trade Business that produces Broccoli and Red Spinach Vegetable ice cream. Community service activities are carried out with training methods in practice and theory. For two days, the community members were invited to understand the purpose, benefits and application of healthy processed broccoli vegetables as a nutritious processed food and economic value. Presentation of learning material related to the importance of community empowerment through an independent learning process, this group is carried out in accordance with the material, goals and practical benefits of each theme. At the last session, this community service activity was presented with a demonstration of cooking food, processing broccoli and red spinach vegetables into healthy, practical ice cream and liked by all people. The activity of processing broccoli and red spinach vegetables as raw materials to obtain these types of food is done by demonstration method while providing explanations that must be mastered when going to process red spinach and broccoli into healthy food for the family, and economic value.Keyword : Broccoli Vegetables, Red Spinach, Vegetable Ice Cream